Transmembrane Segment 3 of Drosophila melanogaster Odorant Receptor Subunit 85b Contributes to Ligand-Receptor Interactions - Nichols, Andrew S. (American Society for Biochemistry and Molecular Biology, 2010)
The OR class insect odorant receptors are ligand-gated ion channels comprised of at least one common subunit (OR83b in Drosophila) and at least one putative odorant-binding subunit. However, little else is known about the molecular details of insect OR architecture. For example, nothing is known about how these receptors bind odorants, greatly limiting efforts to develop insect OR-targeted compounds for the control of insects involved in disease propagation and agricultural damage. Here we identify a portion of a Drosophila OR that is involved in odorant activation of the receptor. Using the substituted cysteine accessibility method, we identified residues 146–150 of OR85b, located at the predicted interface between transmembrane segment 3 (TMS3) and extracellular loop 2 (ECL2), as playing a role in odorant (2-heptanone) activation. We found that occupation of the receptor by the competitive antagonist 2-nonanone protected the receptor from methanethiosulfonate action at position 148, placing this region close to the odorant-binding site. In addition, mutations at positions 142 and 143 within TMS3 altered odorant sensitivity. Our results identify the involvement of the extracellular half of TMS3 in Drosophila OR85b in odorant activation of the receptor. This finding can serve as a starting point for future detailed analysis of the molecular basis for odorant recognition by insect ORs, a novel class of ligand-gated channel.